About the Tunguska harp from the materials of M.N. Zhirkov based on archival data and drawings by P.V. Sleptsov, E.M. Shaposhnikov, E.P. Shestakov - Pavlova-Borisova, Tat'yana Vladimirovna; Borisova, Aitalina Andrianovna (Философия и культура, 2025)
The article is devoted to the Tunguska harp from M.N. Zhirkov's study "Yakut folk music", information about which the composer learned from Khatango-Anabar materials collected by the ethnographer P.V. Sleptsov in the 1920s. The author examines the described harp, taking into account the peculiarities of the ethnogenetic processes of formation of the Dolgan ethnic group, which actively took place in the first half of the twentieth century, which included, among other things, the Evenk clans that roamed in the north of Yakutia. The subject of the study is a sample of a harp, a traditional musical instrument described in the literature as the "Tunguska harp". The object of the study is the traditional musical instruments of the Tungusovs, Dolgans, and Yakuts using the example of materials studied by P.V. Sleptsov, M.N. Zhirkov, and sketched by E.M. Shaposhnikov and E.P. Shestakov.    Since the sources were the collections of these researchers, the collection of Yakut khomuses of the Museum and the Khomus Center of the Peoples of the World (Yakutsk) used methods of observation, comparison and typology. The main conclusions of the conducted research are the following conclusions: - M.N. Zhirkov, in his study "Yakut Folk Music", identified the instrument in P.V. Sleptsov's drawing as the Tunguska harp, since dulgan is the self–name of the Evenki (Tunguska) clan that lived on the territory of Khatanga and Anabar and subsequently participated in the formation of dolgan as a separate northern in the first third of the twentieth century. ethnic group; - the characteristic decor and manufacturing technique of this sample serve the purpose of improving its design with decorative elements and primarily carried aesthetic functions; - information about the Dulgan bargan from the collection of P.V. Sleptsov, the Tunguska harp from the materials of M.N. Zhirkov is of great interest, as they have undoubted similarities with some types of Yakut metal arc clamps of the second half of the twentieth and the first quarter of the twenty-first centuries; - the Yakut hose manufacturers of the second half of the twentieth century are guided by the images given in the work of M.N. Zhirkov "Yakut folk Music" as reference and produce modern Yakut hose with a similar design, without the use of copper trim, but with sound production sufficient not only for chamber music, but also for concert performance.